Belize : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Director for Belize. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues of the Belize economy. The economic condition of Belize is characterized by sluggish growth and a weak fiscal stance, which have put public debt on an unsustainable path. Social and poverty challenges remain significant. The unemployment rate remains high compared with its 2008 level of 8 percent, despite a reduction to 12.1 percent in September 2014 from 14.2 percent in September 2013. Per capita GDP remains far below its regional peers. This paper also focuses on measures that would signal credible commitment to fiscal consolidation, strengthen the financial system, and boost economic, growth taking into account constraints on human and financial resources.